Effects of increasing dried distiller’s grains on feed intake - Hastad, C.W.; Frantz, N.Z.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Recent studies have shown that dried distiller’s grains with solubles (DDGS) has an ME value similar to that of corn, but pigs fed diets with DDGS have a lesser feed intake than do those fed corn. We conducted three studies to evaluate the effects of DDGS on palatability and feed intake of growing pigs. In Exp. 1, 90 gilts (initially 58.2 lb) were used to evaluate the effects of a diet based on cornsoybean meal, alone or with 30% DDGS from two different sources, on feed preference. Source 1 DDGS was obtained from an ethanol plant built before 1990 and source 2 was obtained from a plant built after 1990. Each pen of pigs had two feeders, one with the cornsoybean meal diet and the other with one of the DDGS sources. There were 10 pens with six pigs per pen and 10 pens with 3 pigs per pen, for a total of 90 gilts; all pigs were blocked by weight. The location of the feeders was moved morning and evening each day. From d 0 to 7, there were no differences in ADFI among the dietary treatments. From d 7 to 13 and overall (d 0 to 13), however, feed intake was less (P<0.01) for both DDGS diets, when compared with the corn-soybean control. In Exp. 2, 187 barrows and gilts (initially 52.1 lb) were used to examine the effects of increasing DDGS (source 2) in a 21-d preference study. Treatments consisted of a control diet based on corn-soybean meal, or the control diet with 10, 20, or 30% DDGS. There were 17 pigs per pen and 11 pens. There were four feeders in each pen, each containing a different diet, and the feeders were moved every morning and evening during the trial. During each week for the overall trial, increasing DDGS decreased (linear; P<0.001) ADFI. In Exp. 3, 120 barrows and gilts (initially 41.7 lb) were used to examine the effects of Sucram®, a feed flavor additive, in cornsoybean meal diets, with and without 30% DDGS (source 2), on feed intake in a 21-d preference study. Treatments consisted of a control diet based on corn-soybean meal, or the control diet with 30% DDGS, both with or without Sucram®. There were 15 pigs per pen and 8 pens. Each pen contained all four dietary treatments in individual feeders and the feeders were moved every morning and evening during the trial. For the entire trial, adding DDGS to diets decreased (P<0.001) ADFI. Adding Sucram® had no effect (P>0.33) on feed intake in either the cornsoybean meal or DDGS diets. These studies demonstrate that pigs prefer corn-soybean diets to diets containing DDGS. For these experiments, the source of DDGS or the addition of a feed flavor did not change palatability. Although it seems that the ME content of DDGS could be comparable to that of corn, palatability problems may affect pig performance, even when DDGS included at low rates in the diet.
Keywords: Swine; Pigs; Feed intake; DDGS